IMF Survey, Volume 37, Issue 12. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2008)
Global financial crisis, Iceland, Poul Thomsen, IMF work program, IMF Shocks Facility, Kyrgyz Republic; Malawi; Exogenous Shocks Facility, Pakistan loan, IMF and social safety nets, gains against poverty in jeopardy, commodity prices slump, Latin America withstands shocks, Improved policies help Latin America, Asian Regional Outlook, Bosnia and Herzegovina, news briefs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet